Cloud security for dummies - Coombs, Ted (For Dummies, 2022)
Embrace the cloud and kick hackers to the curb with this accessible guide on cloud security Cloud technology has changed the way we approach technology. It's also given rise to a new set of security challenges caused by bad actors who seek to exploit vulnerabilities in a digital infrastructure. You can put the kibosh on these hackers and their dirty deeds by hardening the walls that protect your data. Using the practical techniques discussed in Cloud Security For Dummies, you'll mitigate the risk of a data breach by building security into your network from the bottom-up. Learn how to set your security policies to balance ease-of-use and data protection and work with tools provided by vendors trusted around the world. This book offers step-by-step demonstrations of how to: Establish effective security protocols for your cloud application, network, and infrastructure Manage and use the security tools provided by different cloud vendors Deliver security audits that reveal hidden flaws in your security setup and ensure compliance with regulatory frameworks As firms around the world continue to expand their use of cloud technology, the cloud is becoming a bigger and bigger part of our lives. You can help safeguard this critical component of modern IT architecture with the straightforward strategies and hands-on techniques discussed in this book.
Includes index. - Description based on print version record
Keywords: Cloud computing -- Security measures; Computer networks -- Security measures; Computer security; Computer Security; Infonuagique; Sécurité; Mesures; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; Computer networks; Security measures; Instructional and educational works; Matériel d'éducation et de formation